Hygienic Assessment of the Impact of Information Attacks on Human Health in the Process of Globalization (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article says that a mobile phone is a source of electromagnetic radiation that directly harms human health, while electromagnetic waves stimulate changes at the cellular level, causing disturbances in the gene sequence, as well as the formation of diseased cells and tumors. The article also discusses preventive measures for the use of a mobile phone.